Chronic skin inflammation leads to bone loss by IL-17-mediated inhibition of Wnt signaling in osteoblasts - Uluckan, Oezge; Jimenez, Maria; Karbach, Susanne; Jeschke, Anke; Grana, Osvaldo; Keller, Johannes; Busse, Bjoern; Croxford, Andrew L.; Finzel, Stephanie; Koenders, Marije; Van Den Berg, Wim; Schinke, Thorsten; et al. (Science Translational Medicine, 2016)
Inflammation has important roles in tissue regeneration, autoimmunity, and cancer. Different inflammatory stimuli can lead to bone loss by mechanisms that are not well understood. We show that skin inflammation induces bone loss in mice and humans. In psoriasis, one of the prototypic IL-17A-mediated inflammatory human skin diseases, low bone formation and bone loss correlated with increased serum IL-17A levels. Similarly, in two mouse models with chronic IL-17A-mediated skin inflammation,K14-IL17A(ind)andJunB(?ep), strong inhibition of bone formation was observed, different from classical inflammatory bone loss where osteoclast activation leads to bone degradation. We show that under inflammatory conditions, skin-resident cells such as keratinocytes, ?? T cells, and innate lymphoid cells were able to express IL-17A, which acted systemically to inhibit osteoblast and osteocyte function by a mechanism involving Wnt signaling. IL-17A led to decreased Wnt signaling in vitro, and importantly, pharmacological blockade of IL-17A rescued Wnt target gene expression and bone formation in vivo. These data provide a mechanism where IL-17A affects bone formation by regulating Wnt signaling in osteoblasts and osteocytes. This study suggests that using IL-17A blocking agents in psoriasis could be beneficial against bone loss in these patients.
EVALuna2:13277